2014
DOI: 10.1007/s40489-014-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Goal Setting Interventions: Implications for Participants on the Autism Spectrum

Abstract: Single-case research design studies that included a goal setting component in interventions for a broad array of participants engaged in a learner role were reviewed. A systematic search of the empirical literature identified 38 studies that met the inclusion criteria. These studies were evaluated in terms of participant characteristics, who set the goals (self or other), how goals were incorporated into interventions, type of behavior change goal setting was applied to and whether maintenance and generalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Figarola et al (2008) found that goal setting, combined with the self-monitoring of progress, leads to improved math fact automaticity for elementary school students with mild intellectual disabilities. For persons with autism spectre disorders, research suggests that interventions which include a self-set goal component may improve independent functioning (Carr, Moore, and Anderson 2014). Codding, Lewandowski, and Eckert (2005) further found that student-selected goals and performance feedback were effective in increasing math fluency in elementary school students with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Figarola et al (2008) found that goal setting, combined with the self-monitoring of progress, leads to improved math fact automaticity for elementary school students with mild intellectual disabilities. For persons with autism spectre disorders, research suggests that interventions which include a self-set goal component may improve independent functioning (Carr, Moore, and Anderson 2014). Codding, Lewandowski, and Eckert (2005) further found that student-selected goals and performance feedback were effective in increasing math fluency in elementary school students with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…When persons with ASD identify social goals for themselves, it is likely that they will have an autonomous motivation for these self-chosen goal, making goal attainment more within reach. Indeed, research has shown that students are more engaged and persistent in the learning process when working on goals of which they perceive a personal value (Carr, Moore, and Anderson 2014).…”
mentioning
confidence: 99%
“…Carr, Moore, and Anderson (2014a) pointed out goal setting as another important component in a self-management intervention for students with ASD for their future success in higher education and vocational settings. They also called for research to evaluate various ways of teaching goal setting in a self-management intervention.…”
mentioning
confidence: 99%